Effect of radiofrequency shield diameter on signal‐to‐noise ratio at ultra‐high field MRI. Issue 6 (19th January 2021) - Zhang, Bei; Adriany, Gregor; Delabarre, Lance; Radder, Jerahmie; Lagore, Russell; Rutt, Brian; Yang, Qing X.; Ugurbil, Kamil; Lattanzi, Riccardo
Abstract : Purpose: In this work, we investigated how the position of the radiofrequency (RF) shield can affect the signal‐to‐noise ratio (SNR) of a receive RF coil. Our aim was to obtain physical insight for the design of a 10.5T 32‐channel head coil, subject to the constraints on the diameter of the RF shield imposed by the head gradient coil geometry. Method: We used full‐wave numerical simulations to investigate how the SNR of an RF receive coil depends on the diameter of the RF shield at ultra‐high magnetic field (UHF) strengths (≥7T). Results: Our simulations showed that there is an SNR‐optimal RF shield size at UHF strength, whereas at low field the SNR monotonically increases with the shield diameter. For a 32‐channel head coil at 10.5T, an optimally sized RF shield could act as a cylindrical waveguide and increase the SNR in the brain by 27% compared to moving the shield as far as possible from the coil. Our results also showed that a separate transmit array between the RF shield and the receive array could considerably reduce SNR even if they are decoupled. Conclusion: At sufficiently high magnetic field strength, the design of local RF coils should be optimized together with the design of the RF shield to benefit from both near field and resonant modes.